O Protocolo de Kyoto: a União Européia na liderança do regime de mudanças climáticas - Domingos, Nicole de Paula (2007)
This research analyzes the factors that led the European Union to adopt a strategy of leadership during the multilateral negotiations on climate change issues, especially after the United States´ refusal to ratify the Kyoto Protocol in 2001. This dissertation points out that the European position should be understood by two central dimensions. The first discusses the economic-energetic context of the bloc and suggests that the pro-Kyoto posture is influenced not only by the deepening economic integration, but also by the necessity of improving the security of energy supply in the European continent. The second dimension makes use of international political debates to demonstrate that this strategy could be perceived as a form to consolidate the Europeans´ international capacity to act as a bloc. Particularly, it is remarkable that the European leadership has been taking place especially in areas where the North-Americans have been progressively disengaged